DIGITAL TRANSFORMATION AND COPYRIGHT AS FIDUCIARY SECURITY: LEGAL, ECONOMIC AND TECHNOLOGICAL PERSPECTIVES - Haspada, Deny (Journal of Social and Economics Research, 2024)
This study explores the viability of using copyright as fiduciary collateral in the digital era, focusing on the legal and technological challenges that arise. The research aims to understand how digital transformation affects the application of copyright as collateral and to identify the legal and technical obstacles involved. A mixed-methods approach was employed, combining qualitative legal analysis with quantitative data from industry surveys and case studies. The findings indicate that while the concept of copyright as collateral is theoretically viable, significant legal and technological barriers hinder its practical implementation. Key challenges include the ambiguity of legal frameworks, the complexity of valuing digital copyrights, and the risks associated with digital piracy and infringement. The study concludes that for copyright to be effectively used as fiduciary collateral, there needs to be a harmonization of international legal standards and advancements in technology to secure and manage digital rights. These findings have important implications for policymakers, legal practitioners, and financial institutions, suggesting the need for reforms and innovations to support the use of intellectual property in financial transactions.